PENGEMBANGAN MEDIA PEMBELAJARAN ELECTRICAL REFRIGERATION AND AIR CONDITIONER DI SMK NEGERI 1 DENPASAR - I Made Adi Pramana; Agus Adiarta; I Gede Ratnaya (Universitas Pendidikan Ganesha, 2021)
This study aims to develop Learning Media for Electrical Refrigeration and Air Conditioner at SMK Negeri 1 Denpasar which will be used to support the learning process in the subject of Refrigeration Control and Air Conditioning in class XI of Cooling and Air Conditioning Engineering. This research is included in the type of research and development or R&D (Research and Development). In this study, percentage statistical data analysis techniques were used to process data from content experts and media experts, while for student responses, standard five-scale data analysis techniques were used. Data was obtained by distributing questionnaires containing statement items. The results obtained in this study are: The content expert test results get a percentage of 95.45% with very proper qualifications, the media expert test results get a percentage of 96.05% with very decent qualifications. The range of small group trial scores with a total of 6 students of class XI TPTU got very high qualifying results and the large group trial scores of 28 students of class XI TPTU got very high qualifying results. Learning Media of Electrical Refrigeration and Air Conditioner at SMK Negeri 1 Denpasar is suitable for use in the learning and teaching process in class XI of Refrigeration and Air Conditioning Engineering at SMK Negeri 1 Denpasar which is applied to the subject of Refrigeration Control and Air Conditioning.